PENGARUH KOMPENSASI, DISIPLIN, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi Pada PT. PLN (Persero) Area Pemeliharaan Jaringan Semarang) - Theresia Adi Irawati, 11.05.51.0060 (Students Journal of Economic and Management, 2015)
This study examines the effect of compensation, discipline, and work motivation of the employees performance.This research was conducted in the Office of PLN (Persero) APJ Semarang. The population of this research consisted of 250 people with a sample of 154 people. Data obtained directly from the source. The technique used for primary data collection is done by means of questionnaires to the respondents. The test results of determination (R2) indictes that employee performance can be explained by the Compensation, Discipline, and Work motivation by 54,5% while the test is influenced by other variables outside of research. Compensation, labor and Discipline, Work Motivation jointly significant effect on employee performance. The result of regression analysis show that, Compensation has positive and significant impact on employee performance, discipline positive and significant effect on the performance of employee, and work motivation positive and significant impact on employee performance. Keywords: Compensation, Discipline, Work Motivation, and Employee Performance